Analysis of multiple choice questions (MCQ): important part of assessment of medical students - Mehta, Maulin; Banode, Siddharth; Adwal, Sandeep (International Journal of Medical Research and Review, 2016)
Background: Assessment influences students learning process that is why analysis of assessment allows us to conduct it properly and accurately. Tarrant M et al. and few others had done similar studies in past. Further studies are required to support the same and continuing awareness among teachers about better assessment of students. Methods: The observational, non-interventional and prospective study was carried out to analyse 100 MCQs used for assessment of 2nd MBBS students. All MCQs were having single stem with four options, one being correct and other three distractors. Each MCQ was analyzed with three tools that were Difficulty Index (DIF I), Discrimination Index (DI) and Distracter Efficiency (DE). Chi square test was used for statistical analysis. Results: Total 74 out of 100 MCQs (74%) were recommended (30-70%) according to DIF I. According to DI, total 34 out of 100 MCQs were good (0.25-0.35) and 30 MCQs were excellent (>0.35). There were 18 non-functional (6%) distractors out of total 300. In none of the MCQs, all three were poor distractor. Association between difficulty index and discrimination index was statistically significant according chi-square test. (p value< 0.05) Conclusions: Properly constructed MCQs, according to these analysis tools, are best for student’s assessment.